2 - Higher Education in South Africa: Market Mill or Public Good? - Vally, Salim (Journal of Higher Education in Africa, 2006)
This paper argues that current trends in higher education entail a disincentive for universities to enrol students from poor backgrounds and the continuing reproduc- tion of a highly elitist system. The perception of success in the marketplace, shrink- ing allocations to education, and a discourse of efficiency and competitiveness have sidelined previous commitments to access, equity and genuine transformation. These developments follow a global market utopia which sees higher education as a com- modity, emphasising a new managerialism spurred on by ‘by market-driven notions of competition, privatisation and consumption that adopt corporate models of man- agement in order to reduce costs and maximise profits’ (Baatjes 2005:29). I draw our attention to the urgency of tasks necessary to prevent the further corporatisation of higher education institutions. Unfulfilled promises by the state and the enormity of tasks ahead can result in a temptation to despair on the part of those who perceive of a different higher education system. The inroads of neo-liberalism, of markets and individualism over social justice, community and solidarity, create new moral imperatives. It is ‘part of a more general re-working of education as a sphere of ethical practice – a commodification of education and values which allows us to systematically neglect the outcomes of policy and practices – a demoralisation of society’ (Ball 2003:25). In this situation, education degenerates into a lucrative market opportunity for capital. However, drawing on my keynote address to the 12th World Congress on Comparative Education in Havana, Cuba, I argue for the cultivation of hope in conjunction with the conviction that there is space for social action. I conclude by arguing that this is essential, since education for the commonweal is too important to be left in the hands of business, and the whims and vicissitudes of the market place.